Conductive electrodes of metallic-organic compound CH3CuS nanowires for all-solid-state flexible supercapacitors. Issue 14 (6th April 2021) - Wang, Xiaodan; Lu, Yao; Zhao, Haofei; Sun, Yinghui; Wang, Rongming
Abstract : Flexible and conductive electrodes are one of the most important components for flexible supercapacitor.  Herein, a flexible supercapacitor device based on CH3 CuS nanowire electrodes was fabricated. Abstract : Development of wearable electronics puts forward higher requirements for flexible energy storage devices. Lighter and thinner electrodes with high conductivity are one of the key factors to meet this demand. Herein, a conductive paper-based electrode, assembled from metallic-organic compound CH3 CuS nanowires prepared by a one-step thermal solution process, is reported. By using the conductive electrodes of CH3 CuS nanowires, the fabricated all-solid-state supercapacitor device delivers an excellent electrochemical performance: an areal capacitance of 90.5 μF cm −2 at a current density of 0.5 mA cm −2, an energy density of 5.2 μW h cm −2, and 98% retention of initial capacitance after undergoing 10 000 cycles. In particular, the fabricated all-solid-state supercapacitor device can work normally under a bent state. The no-additive, cost-effective, and eco-friendly paper-based electrodes present a potential application prospect in the field of flexible energy storage devices.